Voluntariness OF CONSENT TO RESEARCH: A Conceptual Model - Appelbaum, Paul S. (The Hastings Center report, 2009)
A good deal of policy and practice in human subjects research aims to ensure that when subjects consent to research, they do so voluntarily. To date, however, voluntariness and its impairment have been poorly conceptualized and studied. The legal doctrine of informed consent could provide a useful model.